Ensinagem de cálculo às equações de Maxwell no ensino médio: proposta extracurricular à luz da aprendizagem significativa - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The proposal of this dissertation is the development of an extracurricular project that meets the demand of students that are about to conclude high school, of notable knowing in mathematics and physics, specifically in basic electromagnetics. Using the theory of meaningful learning of David Ausubel, the proposal of this project is to incorporate through expositive classes concepts of differential and integral calculus, dot product and vector product of higher education exact sciences courses to the high school environment in order to help high school students that present resourcefulness in exact sciences and yearn for new knowledge. Such mathematical tools presented are going to serve as prior organizers, according to the meaningful learning theory, to the understanding of the pool of the four most influential equations of electromagnetism as a whole: Maxwell's equations. The immediate solutions of Maxwell's equations allow students to link new concept with subsumers already acquired in their regular classes, providing a more detailed view of formulas and concepts only quoted before without any previous reference. In this sense, the goal of this dissertation is not to teach the whole concepts pertinent to higher education, but sharpen the interest for the study area, which is already shown by most students interested in joining exact sciences, engineering courses and similars. Hence, the project improves the performances of apprentices in higher education entrance exams and foments interest in subjects which are classified as boring and difficult both to teach and to learn for most students, although fascinating.
Learning of calculus to Maxwell's equations in high school: extracurricular proposal in the light of meaningful learning
Keywords: Ensino de física; Cálculo diferencial e integral; Equações de Maxwell; Physics education; Differential and integral calculus; Maxwell’s equations; CIENCIAS EXATAS E DA TERRA::FISICA